POTENTIAL ANALYSIS OF VEGETATION TYPES DIVERSITY IN RECLAMATION LANDS POST COAL MINING PT. BUKIT ASAM (pesero) TBK - Yuningsih, Lulu; arez, Arez; Lensari, Delfy (Universitas Muhammadiyah Palembang, 2021)
To overcome the problem of land degradation due to mining is reclamation (revegetation). This study aims to analyze the level of diversity of vegetation types in post-coal mining reclamation land in 2009, 2012 and 2015. Identification and measurement of vegetation parameters using the path or transect method of analyzing vegetation data and species diversity. The potential level of vegetation species diversity shows that the diversity index value of vegetation species in the 2009 planting year is relatively low, namely at the understorey level, seedlings and saplings, at the pole level and trees are classified as moderate with a value of 1.65. Whereas the rare type is relatively low, only the seedling level is classified as medium with a diversity value of 1.52. The index value for the diversity of vegetation types in 2012 for the thick type was relatively low, only at the pole level, which was classified as medium with a value of 1.66. In the relatively low sparse type only the level of understorey, seedlings and saplings can be calculated with the highest diversity value of 1.55. The value of the diversity index for vegetation types in the 2015 planting year for thick and sparse types was relatively low with the highest diversity index value of 1.04.